Fretting fatigue performance optimization method based on plastic layer regulation and control

By using a method based on plastic layer control, different laser energies are used to strengthen the surface of the test piece. Combined with fretting fatigue test, the influence relationship between laser energy and fretting fatigue life is established, and the laser energy parameters are optimized. This solves the problem of limited improvement of fretting fatigue performance in the existing technology, and realizes the extension of component life and improvement of fatigue resistance.

CN120843987APending Publication Date: 2025-10-28NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510845491.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In existing technologies, there is a lack of effective parameter control methods during laser strengthening, resulting in limited improvement in the fretting fatigue performance of nickel-based superalloy parts.

Method used

By using a method based on plastic layer control, the surface of the fretting contact area of ​​the test piece is strengthened by different laser energies to obtain strengthened parts with different plastic layers. Combined with fretting fatigue test, the influence relationship between laser energy and fretting fatigue life is established, and the target laser energy is optimized.

Benefits of technology

It significantly improves the accuracy and operability of laser strengthening parameter control, extends the service life of parts, and enhances fatigue resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120843987A_ABST
    Figure CN120843987A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aero-engine design, and provides a plastic layer regulation-based fretting fatigue performance optimization method, which comprises the following steps: carrying out surface strengthening on a fretting contact area of a test piece based on a plurality of laser energies to obtain a plurality of strengthened pieces; performing a fretting fatigue test on the plurality of reinforcing parts to obtain crack information of the plurality of reinforcing parts; determining a first influence relationship between the laser energy and the fretting fatigue life based on the multiple pieces of laser energy and the crack information; and based on the first influence relationship, determining target laser energy from the multiple pieces of laser energy. According to the method, different laser energies are adopted to perform surface strengthening on the fretting contact area of the test piece to obtain the strengthened piece with different plastic layer characteristics, and the crack propagation characteristics are obtained by combining the fretting fatigue test, so that the influence relationship between the laser energy and the fretting fatigue life is established, and the target laser energy is selected from the influence relationship; optimized selection of laser energy is achieved, and the anti-fatigue performance is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aero-engine design technology, and in particular to a method for optimizing fretting fatigue performance based on plastic layer control. Background Technology

[0002] Nickel-based powder superalloys are widely used in hot-section components of aero-engines due to their excellent high-temperature strength, oxidation resistance, and uniform microstructure. However, in actual operation, these components are often subjected to the combined effects of high-frequency vibration and contact loads, leading to minute relative sliding in the contact area and thus inducing fretting fatigue. Fretting fatigue refers to the premature failure of materials caused by the combined effects of contact stress and cyclic loads when two contact surfaces slide relative to each other under small amplitude vibrations. This phenomenon is widespread in mechanical systems such as aero-engine blades and wheel hub connections, seriously affecting the service life and safety of structural components.

[0003] Currently, efforts to improve the fretting fatigue performance of nickel-based superalloy parts mainly focus on surface modification, coating deposition, and residual stress control. For example, shot peening and laser shock peening are widely used to introduce surface compressive residual stress, thereby delaying crack initiation; among these, laser surface strengthening technology has attracted widespread attention due to its advantages such as strong controllability, high efficiency, and wide applicability.

[0004] However, different laser energies input can affect the characteristics of the formed plastic layer, thus influencing fretting fatigue behavior to varying degrees. Currently, there is a lack of effective parameter control methods for optimizing fretting fatigue resistance during laser strengthening, resulting in limited improvement in fatigue resistance. Summary of the Invention

[0005] This invention provides a method for optimizing fretting fatigue performance based on plastic layer regulation, in order to solve the problem of limited improvement of fatigue performance in the prior art.

[0006] This invention provides a method for optimizing fretting fatigue performance based on plastic layer regulation, comprising: The surface of the micro-motion contact area of ​​the test piece is strengthened by multiple laser energies, resulting in multiple strengthened parts with different plastic layers; the plastic deformation characteristics of the plastic layer of the multiple strengthened parts correspond to the corresponding laser energy. Fretting fatigue tests were performed on the multiple reinforced components to obtain crack information of the multiple reinforced components; the crack information includes crack propagation characteristics; Based on multiple laser energies and crack information from multiple reinforced components, the primary influence relationship between laser energy and fretting fatigue life was determined. Based on the first influence relationship, the target laser energy is determined from the plurality of laser energies.

[0007] According to the present invention, a fretting fatigue performance optimization method based on plastic layer regulation is provided, wherein fretting fatigue tests are performed on the plurality of reinforced parts to obtain crack information of the plurality of reinforced parts, including: Fretting fatigue test is performed on each of the reinforced components to obtain image data of the fretting contact area. The image data is used to indicate multiple images of the fretting contact area from crack initiation to crack propagation. Based on the image data, the crack propagation characteristics of the corresponding reinforced component are determined; wherein, the crack propagation characteristics include the initial crack growth angle, the crack growth angle after deflection, and the crack length under polarization.

[0008] According to the present invention, a method for optimizing fretting fatigue performance based on plastic layer regulation, wherein determining the first influence relationship between laser energy and fretting fatigue life based on multiple laser energies and crack information of multiple strengthening components includes: A second influence relationship between laser energy and the plastic deformation characteristics of the plastic layer is obtained; wherein, the plastic deformation characteristics include grain size; Based on the initial crack growth angle, the crack growth angle after deflection, and the crack length during polarization, the crack growth rate of multiple strengthening components is determined. Based on the crack growth rate of the multiple reinforcing members and the plastic deformation characteristics of the plastic layer, a third influence relationship between the plastic deformation characteristics of the plastic layer and the crack growth rate is determined. Based on the second and third influence relationships, a first influence relationship between the laser energy and the fretting fatigue life is determined.

[0009] According to the present invention, a method for optimizing fretting fatigue performance based on plastic layer modulation is provided, wherein determining the first influence relationship between the laser energy and the fretting fatigue life based on the second influence relationship and the third influence relationship includes: The second influence relationship was determined to be negative. The third influencing relationship was determined to be negative. Based on the second and third influence relationships, the first influence relationship between the laser energy and the fretting fatigue life is determined to be negative.

[0010] According to the present invention, a method for optimizing micro-motion fatigue performance based on plastic layer modulation, wherein determining the target laser energy from the plurality of laser energies includes: The smallest of the plurality of laser energies is determined as the target laser energy.

[0011] According to the present invention, a method for optimizing fretting fatigue performance based on plastic layer modulation, prior to surface strengthening of the fretting contact area of ​​the test piece based on multiple laser energies, the method includes: Determine the preset laser energy range; Multiple laser energies are determined from the preset laser energy range.

[0012] According to the present invention, a method for optimizing fretting fatigue performance based on plastic layer regulation is provided, the method further includes: Obtain microstructure information of the plastic layer of multiple reinforced components; The microstructure information of multiple reinforcing components is simulated and reconstructed to obtain multiple polycrystalline structure models with grain structures on the surface. Based on the equivalent plastic strain value and / or dislocation density of the polycrystalline structure model, the fretting fatigue crack behavior of the polycrystalline structure model is determined. The fretting fatigue crack behavior based on multiple polycrystalline structure models was used to simulate and verify the target laser energy.

[0013] According to the present invention, a method for optimizing fretting fatigue performance based on plastic layer regulation is provided, the method further comprising: Based on the crack information of multiple strengthening components, the strain distribution of different plastic layers was obtained; Based on the strain distribution of different plastic layers, a predictive model for the fretting fatigue performance of plastic layers is constructed.

[0014] The present invention also provides a parameter determination device based on the regulation of fretting fatigue properties by plastic layer, comprising: The module is used to perform surface strengthening on the micro-motion contact area of ​​the test piece based on multiple laser energies, resulting in multiple strengthened parts with different plastic layers; wherein, the plastic deformation characteristics of the plastic layers of the multiple strengthened parts correspond to the corresponding laser energies; The module is used to perform fretting fatigue tests on the multiple reinforced components to obtain crack information of the multiple reinforced components; the crack information includes crack propagation characteristics; The first determining module is used to determine the first influence relationship between laser energy and fretting fatigue life based on multiple laser energies and crack information of multiple strengthening components. The second determining module is used to determine the target laser energy from the plurality of laser energies based on the first influence relationship.

[0015] The present invention also provides an electronic device, including a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the computer program to implement the micro-motion fatigue performance optimization method based on plastic layer regulation as described above.

[0016] The present invention provides a method for optimizing fretting fatigue performance based on plastic layer control. By using different laser energies to strengthen the surface of the fretting contact area of ​​the test piece, reinforced parts with different plastic layer characteristics are obtained. By combining fretting fatigue tests to obtain crack propagation characteristics, the influence relationship between laser energy and fretting fatigue life is established, and the target laser energy is selected from the results to achieve optimized laser energy selection. It can be seen that this method can effectively correlate the correspondence between plastic layer characteristics and fretting fatigue performance, significantly improve the accuracy and operability of laser strengthening parameter control, thereby improving the fatigue resistance of components and significantly extending the service life of parts. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0018] Figure 1 This is one of the flowcharts of the fretting fatigue performance optimization method based on plastic layer regulation provided by the present invention.

[0019] Figure 2 This is the second flowchart of the fretting fatigue performance optimization method based on plastic layer regulation provided by the present invention.

[0020] Figure 3 This is the third flowchart of the fretting fatigue performance optimization method based on plastic layer regulation provided by the present invention.

[0021] Figure 4 This is a schematic diagram of the mating structure of the test specimen and the turbine disk specimen provided by the present invention.

[0022] Figure 5 is a schematic diagram of the fretting fatigue crack initiation and propagation process of the S sample provided by the present invention.

[0023] Figure 6 is a schematic diagram of the fretting fatigue crack initiation and propagation process of the M sample provided by the present invention.

[0024] Figure 7 is a schematic diagram of the fretting fatigue crack initiation and propagation process of the L sample provided by the present invention.

[0025] Figure 8 This is a schematic diagram of the micro-motion fatigue performance optimization device based on plastic layer regulation provided by the present invention.

[0026] Figure 9 This is a schematic diagram of the structure of the electronic device provided by the present invention. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0028] The following is combined with Figures 1-7 The present invention describes a method for optimizing fretting fatigue performance based on plastic layer regulation.

[0029] Embodiments of the present invention propose a method for optimizing fretting fatigue performance based on plastic layer regulation, such as... Figure 1 As shown, the method includes the following steps: Step 100: Surface strengthening of the micro-motion contact area of ​​the test piece is performed based on multiple laser energies to obtain multiple strengthened parts with different plasticity layers.

[0030] Among them, the plastic deformation characteristics of the plastic layer of multiple reinforcing components correspond to the corresponding laser energy.

[0031] It is understandable that by using different laser energies to perform surface strengthening treatment on the micro-motion contact area of ​​the test piece, multiple strengthened parts with different plastic layers can be obtained. As a result, the plastic layers of the multiple strengthened parts are different. The difference in plastic layers is due to the different plastic deformation characteristics (such as depth, hardness distribution and residual stress state). The plastic layer characteristics (plastic deformation characteristics of the plastic layer) of the multiple strengthened parts are related to the laser energy used.

[0032] Step 200: Perform fretting fatigue tests on multiple reinforced components to obtain crack information of multiple reinforced components; crack information includes crack propagation characteristics.

[0033] Understandably, fretting fatigue tests are conducted on all surface-strengthened components to monitor and record crack information such as crack propagation characteristics of each component, providing data support for subsequent analysis.

[0034] Step 300: Based on multiple laser energies and crack information of multiple reinforced components, determine the first influence relationship between laser energy and fretting fatigue life.

[0035] It is understandable that by combining the laser energy corresponding to each strengthening component and the crack information obtained from the fretting fatigue test, the primary influence relationship between laser energy and fretting fatigue life can be established, revealing the quantitative relationship between the two.

[0036] Step 400: Based on the first influence relationship, determine the target laser energy from multiple laser energies.

[0037] Understandably, based on the established first influence relationship, a target laser energy is selected from multiple laser energies to ensure that the optimized laser strengthening process can effectively improve the component's resistance to fretting fatigue, thereby significantly extending the service life of the parts and improving their operational reliability. It should be noted that a component typically refers to a key part in an engineering structure or mechanical equipment that performs a specific function or bears a load; for example, in an aero-engine, blades and rotors are components. Components more broadly encompass all small or large parts assembled into the final product, and can be a complete subsystem within an aero-engine.

[0038] The present invention provides a method for optimizing fretting fatigue performance based on plastic layer control. By using different laser energies to strengthen the surface of the fretting contact area of ​​the test piece, reinforced parts with different plastic layer characteristics are obtained. By combining fretting fatigue tests to obtain crack propagation characteristics, the influence relationship between laser energy and fretting fatigue life is established, and the target laser energy is selected from the results to achieve optimized laser energy selection. It can be seen that this method can effectively correlate the correspondence between plastic layer characteristics and fretting fatigue performance, significantly improve the accuracy and operability of laser strengthening parameter control, thereby improving the fatigue resistance of components and significantly extending the service life of parts.

[0039] It should be noted that the micro-motion fatigue performance optimization method based on plastic layer regulation in this embodiment not only achieves precise control of laser energy parameters, but also provides a scientific basis for selecting the best surface strengthening strategy for specific application needs in engineering practice.

[0040] In one embodiment of the present invention, such as Figure 2 As shown, step 200, performing fretting fatigue tests on multiple reinforced components to obtain crack information for multiple reinforced components, may include the following steps: Step 210: Perform fretting fatigue test on each reinforced component and obtain image data of the fretting contact area. The image data is used to indicate multiple images of the fretting contact area from crack initiation to propagation.

[0041] Understandably, fretting fatigue testing is performed on each reinforced component, and high-precision imaging technology is used to obtain multiple image data of the fretting contact area of ​​the reinforced component from crack initiation to crack propagation. This image data is used to record each stage of crack development.

[0042] Step 220: Based on image data, determine the crack propagation characteristics of the corresponding reinforced component; wherein, the crack propagation characteristics include the initial crack growth angle, the crack growth angle after deflection, and the crack length under polarization.

[0043] Understandably, based on the acquired image data, the crack propagation characteristics of each reinforced component are analyzed and determined, including but not limited to key parameters such as the initial crack growth angle, the crack growth angle after deflection, and the crack length under polarization. Through quantitative analysis of these crack propagation characteristics, the influence of different plastic layer characteristics on fretting fatigue behavior can be obtained, providing data support for establishing the relationship between laser energy and fretting fatigue life, and ultimately guiding the optimization of laser strengthening process selection to significantly improve fretting fatigue resistance.

[0044] Optional, such as Figure 3 As shown, step 300, determining the first influence relationship between laser energy and fretting fatigue life based on multiple laser energies and crack information of multiple strengthening components, may include the following steps: Step 310: Obtain the second influence relationship between laser energy and the plastic deformation characteristics of the plastic layer.

[0045] Among them, the plastic deformation characteristics include, but are not limited to, grain size. The grain size of different plastic layers is obtained, and based on multiple laser energies and corresponding multiple grain sizes, the second influence relationship between laser energy and plastic deformation characteristics of plastic layers is determined.

[0046] Step 320: Determine the crack growth rate of multiple strengthening components based on the initial crack growth angle, the crack growth angle after deflection, and the crack length during polarization.

[0047] Understandably, performing fretting fatigue tests on each reinforced component can yield multiple image data from the entire process of crack initiation to propagation. After analysis, the initial crack growth angle, the crack growth angle after deflection, and the crack length under polarization can be obtained. Based on the initial crack growth angle, the crack growth angle after deflection, and the crack length under polarization, the crack growth rate of each reinforced component can be calculated, thereby quantifying the crack propagation behavior pattern under different plastic layer conditions.

[0048] Step 330: Based on the crack growth rate of multiple reinforced components and the plastic deformation characteristics of the plastic layer, determine the third influence relationship between the plastic deformation characteristics of the plastic layer and the crack growth rate.

[0049] Understandably, by analyzing the crack growth rate and plastic deformation characteristics (grain size) of multiple reinforced components, a third influence relationship between the plastic deformation characteristics of the plastic layer and the crack growth rate is established, revealing the influence mechanism of the microstructure of the plastic layer on the crack propagation rate.

[0050] Step 340: Based on the second and third influence relationships, determine the first influence relationship between laser energy and fretting fatigue life.

[0051] Understandably, by combining the obtained second influence relationship (the relationship between laser energy and plastic deformation characteristics) and third influence relationship (the relationship between plastic deformation characteristics and crack growth rate), the first influence relationship between laser energy and fretting fatigue life can be determined, realizing the correlation analysis from laser processing parameters (laser energy) to the final fatigue performance. This not only deepens the optimization of laser surface strengthening process, but also provides a scientific basis and technical path for improving the resistance to fretting fatigue.

[0052] Furthermore, step 340, determining the first influence relationship between laser energy and fretting fatigue life based on the second and third influence relationships, may include the following: The second influence relationship was determined to be negative. The third influence relationship was determined to be negative. Based on the second and third influence relationships, the first influence relationship between laser energy and fretting fatigue life is determined to be negative.

[0053] It is understandable that by analyzing and determining the second influence relationship, the higher the laser energy, the smaller the plastic deformation characteristics of the plastic layer, such as the grain size, will be; the lower the laser energy, the larger the plastic deformation characteristics of the plastic layer, such as the grain size, will be. Therefore, there is a negative correlation between laser energy and the plastic deformation characteristics (grain size) of the plastic layer, that is, the second influence relationship is negative.

[0054] Analysis and determination of the third influence relationship revealed a negative correlation between the plastic deformation characteristics of the plastic layer and the crack growth rate, indicating that plastic deformation characteristics (such as larger grain size) help to slow down the crack propagation rate.

[0055] The faster the crack growth rate, the faster the crack propagates, and the lower the fretting fatigue life. The faster the growth rate and the lower the fretting fatigue life, the more negatively correlated they are.

[0056] Based on the second and third influencing relationships, as well as the relationship between growth rate and fretting fatigue life, it can be deduced that the first influencing relationship between laser energy and fretting fatigue life is negatively correlated. That is, appropriately reducing laser energy can increase the grain size of the plastic layer, reduce the crack propagation rate, and thus extend the fretting fatigue life. Therefore, by selecting low laser energy parameters, the material's resistance to fretting fatigue can be effectively improved, thereby significantly extending its service life.

[0057] It should be noted that plastic deformation characteristics can also include the depth of the plastic layer, which varies with different plastic layers. When obtaining the second influence relationship between laser energy and the plastic deformation characteristics of the plastic layer, it is necessary to distinguish between different plastic deformation characteristics. Specifically, when the plastic deformation characteristic is grain size, the second influence relationship shows a negative correlation, that is, as the laser energy increases, the grain size decreases; when the plastic deformation characteristic is the depth of the plastic layer, the second influence relationship shows a positive correlation, that is, as the laser energy increases, the depth of the plastic layer increases, and the increased plastic layer depth can introduce more residual compressive stress.

[0058] Optionally, in step 400, determining the target laser energy from multiple laser energies may include the following: The smallest of the multiple laser energies is determined as the target laser energy.

[0059] It is understandable that the primary influence relationship between laser energy and fretting fatigue life is negative, thus the minimum laser energy among multiple laser energies is determined as the target laser energy to improve fretting fatigue life.

[0060] In one embodiment of the present invention, prior to step 100, the method further includes the following: Determine the preset laser energy range; from the preset laser energy range, determine multiple laser energies.

[0061] Understandably, before performing step 100, a preset laser energy range suitable for the current working conditions should be determined based on the type of material to be strengthened, the geometric characteristics of the fretting contact area, and the expected surface strengthening effect, combined with existing process experience or preliminary experimental data. The lower limit of this range must ensure effective surface strengthening, while the upper limit must avoid material damage due to excessive energy. Furthermore, it should cover the energy range that may significantly affect the properties of the plastic layer, ensuring that subsequent tests can fully reflect the influence of laser energy changes on fretting fatigue performance. Within the determined preset laser energy range, several representative laser energy values ​​are selected according to a certain gradient or step size as process parameters for subsequent surface strengthening of the test piece.

[0062] For example, the preset laser energy range is 70~150mJ, from which 70mJ, 100mJ and 130mJ are selected as three laser energies.

[0063] In one specific embodiment of the present invention, the tenon connection structure between the turbine disk and the blade of an aero-engine is a typical location of fretting fatigue damage, such as... Figure 4As shown, test piece 410 is designed based on the tenon at the root of the turbine blade, and turbine disk test piece 420 is designed based on the turbine disk. Test piece 410 and turbine disk test piece 420 are fitted with dovetail joints and tenons. The two contact areas between test piece 410 and turbine disk test piece 420 are fretting contact areas. Both the test piece and the turbine disk test piece are made of nickel-based powder alloy FGH96. The optimization method in this embodiment specifically includes the following steps: S1. Surface strengthening of the micro-motion contact area of ​​the test piece is performed based on multiple laser energies to obtain multiple strengthened parts with different plasticity layers.

[0064] Specifically, the micro-motion contact area of ​​the test piece was subjected to surface strengthening treatment using three different laser energies: 70mJ, 100mJ, and 130mJ, respectively, resulting in three strengthened specimens, denoted as S specimen, M specimen, and L specimen.

[0065] S2. Perform fretting fatigue tests on multiple reinforced components to obtain crack information of multiple reinforced components.

[0066] The crack information includes, but is not limited to, crack initiation characteristics and crack propagation characteristics.

[0067] Specifically, the three reinforced components and the matching turbine disk specimen were assembled on a fatigue testing machine for fretting fatigue testing to obtain the crack initiation and crack propagation characteristics of each reinforced component. It should be noted here that... Figure 4 In the process, the ends of the reinforced part (equivalent to the test piece) and the turbine disk test piece, which are far apart from each other, are respectively assembled on the fatigue testing machine. The fatigue testing machine applies a load to the reinforced part to simulate the fretting fatigue of the tenon of the aero-engine in the actual working environment.

[0068] The fretting fatigue crack initiation and propagation process of specimen S is as follows: Figure 5 As shown, Figure 5In the figure, Figure (a) shows the SEM scanning area, which is the area observed on the surface of the micro-motion contact area of ​​the sample using a scanning electron microscope (SEM); Figure (b) is the scan image with N=0 and L=0 μm; Figure (c) is the scan image with N=410023 and L=0 μm; Figure (d) is the scan image with N=412633 and L=315 μm; Figure (e) is the scan image with N=418276 and L=487 μm; Figure (f) is the scan image with N=419447 and L=648 μm; Figure (g) is the scan image with N=420364 and L=794 μm; Figure (h) is the scan image with N=420885. Figure (i) shows the scanned image with N=421368 and L=1013 μm; Figure (j) shows the scanned image with N=421760 and L=1118 μm; Figure (k) shows the scanned image with N=424414 and L=1520 μm; Figure (l) shows the scanned image with N=425497 and L=1760 μm; where N is the fatigue life in cycles and L is the crack length in micrometers. It should be noted that... Figure 5 Figure (a) in the image is an in-situ image before loading, serving as a reference for crack comparison.

[0069] like Figure 5 As shown, at N=410023 cycles, the interface between the precipitate and the matrix detached, and a white precipitate was formed on the surface, along with a small amount of wear debris. At N=424414 cycles, the crack extended to 1520 μm, and the extension direction deflected, indicating that the long crack extension behavior was mainly controlled by the distal tensile force, exhibiting the characteristics of a Type I crack, and L1=1185 μm is the depth of influence of the fretting contact zone.

[0070] The fretting fatigue crack initiation and propagation process of specimen M is as follows: Figure 6 As shown, Figure 6In the figure, Figure (a) shows the SEM scanning area; Figure (b) is the scanned image with N=0 and L=0μm; Figure (c) is the scanned image with N=140311 and L=0μm; Figure (d) is the scanned image with N=144793 and L=389μm; Figure (e) is the scanned image with N=145155 and L=504μm; Figure (f) is the scanned image with N=145526 and L=663μm; Figure (g) is the scanned image with N=145714 and L=733μm; Figure (h) is the scanned image with N=145848 and L=785μm; Figure (i) is the scanned image with N=146076 and L=875μm; and Figure (j) is the scanned image with N=146242. Figure (k) shows the scanned image with N=146598 and L=1130μm; Figure (l) shows the scanned image with N=146958 and L=1338μm.

[0071] like Figure 6 As shown, at N=144793 cycles, a 389μm crack was observed, exhibiting a serrated shape. The initial crack propagation angle was 94.1° with the contact surface (the plane containing the fretting contact area), and after propagating to L2=727μm, as... Figure 6 The middle figure (k) shows a 14° extension.

[0072] The initiation and propagation process of fretting fatigue cracks in specimen L is as follows: Figure 7 As shown; Figure 7 In the figure, Figure (a) shows the SEM scanning area; Figure (b) is the scanned image with N=0 and L=0μm; Figure (c) is the scanned image with N=50901 and L=0μm; Figure (d) is the scanned image with N=195093 and L=472μm; Figure (e) is the scanned image with N=195461 and L=572μm; Figure (f) is the scanned image with N=195851 and L=696μm; Figure (g) is the scanned image with N=196239 and L=813μm; Figure (h) is the scanned image with N=196592 and L=925μm; Figure (i) is the scanned image with N=197387 and L=1101μm; and Figure (j) is the scanned image with N=197559 and L=1140μm. The scanned images are shown in Figure (k), which shows the scanned image with N=197919 and L=1218μm; and Figure (l) shows the scanned image with N=198436 and L=1348μm.

[0073] like Figure 7 As shown, at N=195093, a crack approximately 472 μm long was observed, and the crack was essentially a straight line. Subsequently, around 2000 weeks, the crack rapidly propagated along the straight line to 1348 μm, with the propagation path at an angle of 78.2° to the contact surface.

[0074] Furthermore, in this embodiment, fretting fatigue tests were also conducted on the unstrengthened test specimens. The unstrengthened test specimens were designated as AS specimens. The unstrengthened test specimens exhibited lower resistance to crack initiation during fretting fatigue, cracks were more likely to nucleate and propagate along grain boundaries, and the crack propagation rate was relatively fast, resulting in a shorter overall fretting fatigue life.

[0075] S3. Based on multiple laser energies and crack information of multiple reinforced components, determine the primary influence relationship between laser energy and fretting fatigue life.

[0076] Specifically, in the early stages of crack propagation, the grain refinement caused by the plastic layer is severe, and the crack is affected by the interaction of pressure and friction at the fretting contact surface. The crack propagation direction is generally close to the normal direction of the contact surface. The crack propagation characteristics are shown in Table 1, based on the fretting fatigue crack initiation and propagation process of specimens S, M, and L.

[0077] Table 1

[0078] As shown in Table 1, before the crack deflects, the angle between the crack and the contact plane is generally 90°, indicating that crack propagation is mainly affected by the contact surface pressure and tangential friction, and crack growth is controlled by fretting fatigue load. As the crack length increases, the multiaxial stress field and stress concentration caused by fretting gradually weaken, and the crack fretting contact surface and propagation direction gradually deflect. At this time, the crack direction is generally perpendicular to the tensile load in the far field, showing type I crack propagation, and the propagation direction is at an angle of 50-60° with the contact surface.

[0079] It should be noted that the length of the crack deflection is closely related to the surface-strengthening plastic layer. As can be seen, the fretting influence zone of sample S is much larger than that of samples M and L. Introducing a moderate plastic layer on the surface can significantly increase the propagation stage of small cracks, reduce the propagation rate, and thus significantly improve fretting fatigue life. It is evident that there is a negative correlation between laser energy and fretting fatigue life. High-energy surface treatment induces a plastic layer with deeper and smaller grains, introducing a large number of grain boundaries, leading to an accelerated propagation rate, reduced resistance to small crack growth, and consequently, a reduced fretting influence zone, thus decreasing fretting fatigue life.

[0080] S4. Based on the first influence relationship, determine the target laser energy from multiple laser energies.

[0081] Specifically, based on the negative correlation between laser energy and fretting fatigue life, by selecting a low laser energy of 70mJ, the grain size of the plastic layer can be increased, the crack propagation rate can be reduced, thereby effectively improving the material's ability to resist fretting fatigue and significantly extending its service life.

[0082] Furthermore, the method in this embodiment also includes the following steps: S5. Perform EBSD analysis on fatigue cracks.

[0083] Among them, EBSD analysis, or Electron Backscatter Diffraction analysis, is a technique that uses scanning electron microscopy to study the crystal structure of materials.

[0084] Specifically, after the AS sample was subjected to fretting load and crack formation, EBSD analysis was performed. The dislocation density and small-angle grain boundary density were high on both sides of the crack, indicating that the crack mainly propagated transgranularly. Dislocation and small-angle grain boundary density were enriched along the crack tip propagation direction, indicating the direction in which the crack would grow next. This sample was untreated; almost no dislocations were observed far from the crack, and the average grain size was slightly larger than near the crack.

[0085] EBSD analysis was performed on specimen S (70mJ impact-strengthened specimen) after it was subjected to fretting load and crack formation. Compared with specimen AS, due to the high density of dislocations near the surface formed by laser shock treatment, and the fretting fatigue load cyclic friction, the dislocation density and depth near the surface were significantly increased compared to specimen AS. The dislocation density and small-angle grain boundary density on both sides of the crack were also high. In the early stage of crack development, it almost showed intergranular characteristics, while after 80μm, it showed a transgranular trend. The dislocation density and small-angle grain boundary showed that the crack had a tendency to bifurcate.

[0086] After the M and L specimens were subjected to fretting loads and cracks were formed, EBSD analysis was performed. Due to the increase in crack length, the field of view also increased accordingly, encompassing the entire crack. Similar to the S specimen, the cracks in the M and L specimens were initially perpendicular to the fretting contact surface, and then mainly propagated transgranularly in the depth direction. Crack propagation was mainly transgranular failure in the depth direction. Near the crack, the plastic deformation caused by transgranularity resulted in grain breakage, showing a small average grain size.

[0087] It is evident that cracks primarily initiate at the lower edge of the tenon. In the initial stage of crack initiation, due to the obstruction of grain boundaries, the crack propagates along the grain boundaries. Subsequently, it propagates along the path of lowest energy according to the principle of lowest energy. Further away from the fretting contact zone, crack propagation alternates between intergranular and transgranular propagation, with the intergranular propagation rate exceeding the transgranular propagation rate. The plastic layer structure introduced into samples M and L is deeper and more extensive, with smaller grain sizes. This results in a lower initial crack propagation rate in samples M and L compared to the untreated sample. However, after crack initiation, the excessive reduction in grain size and the presence of numerous grain boundaries accelerate crack propagation, significantly increasing the crack growth rate. Clearly, the plastic layer introduced by the high-energy strengthening process is detrimental to crack propagation behavior. Therefore, the low-energy strengthening process can reduce the crack propagation rate and effectively improve the material's resistance to fretting fatigue.

[0088] In one embodiment of the present invention, the method further includes the step of: Step 500: Simulate and verify the target laser energy.

[0089] Understandably, simulations are performed on the target laser energy selected through the aforementioned steps to evaluate its feasibility and enhancement effect in practical applications.

[0090] Optionally, step 500, simulating and verifying the target laser energy, may include the following steps: Step 510: Obtain microstructure information of the plastic layer of multiple reinforcing components.

[0091] Step 520: Simulate and reconstruct the grains of the microstructure information of multiple reinforcing components to obtain multiple polycrystalline structure models with grain structures on the surface.

[0092] Step 530: Determine the fretting fatigue crack behavior of the polycrystalline structure model based on the equivalent plastic strain value and / or dislocation density of the polycrystalline structure model.

[0093] Step 540: Based on the fretting fatigue crack behavior of multiple polycrystalline structure models, the target laser energy is simulated and verified.

[0094] Understandably, simulation verification of the selected target laser energy is necessary to ensure its practical application effectiveness. Specifically, firstly, microstructural information of the plastic layer of multiple reinforced components treated with different laser energies is acquired. This information includes key features such as grain size, morphology, and distribution. Secondly, this microstructural information is used to simulate and reconstruct the grains in each reinforced component (sample), creating a polycrystalline structure model with realistic grain structure characteristics. This model accurately reflects the actual microstructure of the plastic layer. Then, combining the equivalent plastic strain distribution and dislocation density variation in the polycrystalline structure model, key crack behavior characteristics such as crack initiation location, propagation path, and propagation rate under fretting fatigue loading are analyzed and predicted, revealing the influence of microstructure evolution on the fatigue failure mechanism. Finally, by synthesizing the simulation results of fretting fatigue crack behavior from all polycrystalline models, the effectiveness of the target laser energy in suppressing crack initiation and slowing crack propagation is evaluated, thus completing the simulation verification of the target laser energy parameters. This systematic simulation verification method not only accurately predicts and optimizes the effects of laser surface strengthening processes in a virtual environment but also provides reliable data support and technical guidance for engineering practice.

[0095] In this embodiment, in the numerical simulation study of fretting fatigue of nickel-based superalloys considering the influence of the plastic layer, based on the microstructural information such as grain size obtained from EBSD (Electron Backscatter Diffraction) testing, modeling tools such as DREAM.3D (material microstructure modeling and simulation software) are used in conjunction with automated scripts to accurately reconstruct each grain, thereby constructing a polycrystalline structure model with surface gradient grain characteristics. This model can realistically reflect the gradient plastic layer structure formed on the material surface due to laser strengthening, providing a highly realistic geometric and microstructural basis for subsequent numerical simulation of fretting fatigue behavior. Through this modeling method, the changing trend of the grain structure inside the plastic layer can be effectively reproduced in the contact area, providing support for in-depth analysis of the material fatigue failure mechanism under different laser energy conditions.

[0096] In the simulation analysis of crack initiation behavior, equivalent plastic strain was used as a key indicator to predict the location and trend of crack initiation. Simulation results showed that in samples under three different plastic layer states, the peak value of the equivalent plastic strain appeared in the contact edge region between the fretting sample and the fretting pad. This result is highly consistent with the crack initiation location observed in high-temperature in-situ fretting fatigue tests, verifying the effectiveness of the model. Further analysis revealed that with increasing laser energy, the grain structure gradually refined, the grain size decreased, and the equivalent plastic strain value showed an upward trend. The peak value of the equivalent plastic strain for sample S was 1.132 microstrain, for sample M it was 1.162 microstrain, and for sample L it increased to 1.662 microstrain. This indicates that although grain refinement helps improve material strength, when the grains are too small, it exacerbates local stress concentration, making crack initiation easier and thus reducing crack initiation life.

[0097] Regarding the analysis of crack propagation paths, the study of dislocation density distribution cloud maps revealed that dislocations are mainly concentrated near grain boundaries, which is consistent with the aforementioned phenomenon of small cracks propagating along grain boundaries. The dislocation density inside the grains is relatively low, indicating that under fretting loads, the crack propagation path is mainly controlled by grain boundaries and is significantly affected by multiaxial stress fields and local stress concentrations. With the increase of laser energy, the grains are further refined, and the dislocation density also increases significantly. The peak dislocation density of sample S is lower than that of sample M, while sample L has the highest dislocation density. This trend indicates that although the plastic layer structure is optimized to some extent with the increase of laser energy, the excessive grain refinement restricts dislocation movement and accumulates at grain boundaries, which reduces crack propagation resistance and increases crack propagation rate, thus adversely affecting the material's resistance to fretting fatigue. The above simulation results are consistent with the experimental observation results, verifying the accuracy of the target laser energy parameters.

[0098] In one embodiment of the present invention, the method further includes: Based on the crack information of multiple strengthening components, the strain distribution of different plastic layers is obtained; based on the strain distribution of different plastic layers, a fretting fatigue performance prediction model of the plastic layer is constructed.

[0099] Understandably, based on crack information obtained from fretting fatigue tests of multiple reinforced components treated with different laser energies, the strain distribution characteristics of each plastic layer are analyzed and extracted, including but not limited to key parameters such as strain gradient, maximum strain value, and strain influence depth. By analyzing data such as crack initiation location, propagation path, and propagation rate, the local strain response and stress concentration phenomena of each plastic layer under cyclic loading are revealed. Combined with the material's microstructure (such as grain size and dislocation density), a mapping relationship between the strain distribution of the plastic deformation layer and fretting fatigue crack behavior is established. Furthermore, machine learning algorithms are used to integrate these strain field parameters and fatigue life data to construct a fretting fatigue performance prediction model considering the strain gradient effect. This model can not only simulate and predict the ability of the plastic layer to resist fretting fatigue under different process parameters, but also accurately characterize the process mechanism by which the plastic deformation layer affects fatigue damage accumulation by regulating the degree of local strain concentration.

[0100] The following describes the micro-motion fatigue performance optimization device based on plastic layer regulation provided by the present invention. The micro-motion fatigue performance optimization device based on plastic layer regulation described below and the micro-motion fatigue performance optimization method based on plastic layer regulation described above can be referred to in correspondence.

[0101] Embodiments of the present invention propose a fretting fatigue performance optimization device based on plastic layer regulation, such as... Figure 8 As shown, the device includes a obtaining module 810, an acquisition module 820, a first determining module 830, and a second determining module 840; wherein: Module 810 is obtained, which is used to strengthen the surface of the micro-motion contact area of ​​the test piece based on multiple laser energies, and obtain multiple strengthened parts with different plastic layers; wherein, the plastic deformation characteristics of the plastic layer of the multiple strengthened parts correspond to the corresponding laser energy; The module 820 is used to perform fretting fatigue tests on multiple reinforced components to obtain crack information of the multiple reinforced components; the crack information includes crack propagation characteristics. The first determining module 830 is used to determine the first influence relationship between laser energy and fretting fatigue life based on multiple laser energies and crack information of multiple strengthening components. The second determining module 840 is used to determine the target laser energy from multiple laser energies based on the first influence relationship.

[0102] Figure 9 An example is a schematic diagram of the physical structure of an electronic device, such as... Figure 9As shown, the electronic device may include a processor 910, a communications interface 920, a memory 930, and a communication bus 940, wherein the processor 910, the communications interface 920, and the memory 930 communicate with each other via the communication bus 940. The processor 910 can call logic instructions in the memory 930 to execute a fretting fatigue performance optimization method based on plastic layer regulation. This method includes: surface strengthening of the fretting contact area of ​​the test piece based on multiple laser energies to obtain multiple strengthened parts with different plastic layers; wherein the plastic deformation characteristics of the plastic layers of the multiple strengthened parts correspond to the corresponding laser energies; performing fretting fatigue tests on the multiple strengthened parts to obtain crack information of the multiple strengthened parts; the crack information includes crack propagation characteristics; determining a first influence relationship between laser energy and fretting fatigue life based on the multiple laser energies and the crack information of the multiple strengthened parts; and determining a target laser energy from the multiple laser energies based on the first influence relationship.

[0103] Furthermore, the logical instructions in the aforementioned memory 930 can be implemented as software functional units and, when sold or used as independent products, can be stored in a computer-readable storage medium. Based on this understanding, the technical solution of the present invention, in essence, or the part that contributes to the prior art, or a part of the technical solution, can be embodied in the form of a software product. This computer software product is stored in a storage medium and includes several instructions to cause a computer device (which may be a personal computer, server, or network device, etc.) to execute all or part of the steps of the methods of the various embodiments of the present invention. The aforementioned storage medium includes various media capable of storing program code, such as USB flash drives, portable hard drives, read-only memory (ROM), random access memory (RAM), magnetic disks, or optical disks.

[0104] On the other hand, the present invention also provides a computer program product, which includes a computer program that can be stored on a non-transitory computer-readable storage medium. When the computer program is executed by a processor, the computer can execute the fretting fatigue performance optimization method based on plastic layer regulation provided by the above methods. The method includes: surface strengthening of the fretting contact area of ​​the test piece based on multiple laser energies to obtain multiple reinforced parts with different plastic layers; wherein the plastic deformation characteristics of the plastic layer of the multiple reinforced parts correspond to the corresponding laser energy; performing fretting fatigue tests on the multiple reinforced parts to obtain crack information of the multiple reinforced parts; the crack information includes crack propagation characteristics; determining a first influence relationship between laser energy and fretting fatigue life based on the multiple laser energies and the crack information of the multiple reinforced parts; and determining a target laser energy from the multiple laser energies based on the first influence relationship.

[0105] In another aspect, the present invention also provides a non-transitory computer-readable storage medium storing a computer program thereon, which, when executed by a processor, implements the fretting fatigue performance optimization method based on plastic layer regulation provided by the above methods. This method includes: surface strengthening of the fretting contact area of ​​a test piece based on multiple laser energies to obtain multiple reinforced parts with different plastic layers; wherein the plastic deformation characteristics of the plastic layers of the multiple reinforced parts correspond to the corresponding laser energies; performing fretting fatigue tests on the multiple reinforced parts to obtain crack information of the multiple reinforced parts; the crack information includes crack propagation characteristics; determining a first influence relationship between laser energy and fretting fatigue life based on the multiple laser energies and the crack information of the multiple reinforced parts; and determining a target laser energy from the multiple laser energies based on the first influence relationship.

[0106] The device embodiments described above are merely illustrative. The units described as separate components may or may not be physically separate, and the components shown as units may or may not be physical units; that is, they may be located in one place or distributed across multiple network units. Some or all of the modules can be selected to achieve the purpose of this embodiment according to actual needs. Those skilled in the art can understand and implement this without any creative effort.

[0107] Through the above description of the embodiments, those skilled in the art can clearly understand that each embodiment can be implemented by means of software plus necessary general-purpose hardware platforms, and of course, it can also be implemented by hardware. Based on this understanding, the above technical solutions, in essence or the part that contributes to the prior art, can be embodied in the form of a software product. This computer software product can be stored in a computer-readable storage medium, such as ROM / RAM, magnetic disk, optical disk, etc., including several instructions to cause a computer device (which may be a personal computer, server, or network device, etc.) to execute the methods of various embodiments or some parts of embodiments.

[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for optimizing fretting fatigue performance based on plastic layer regulation, characterized in that, include: The surface of the micro-motion contact area of ​​the test piece is strengthened by multiple laser energies, resulting in multiple strengthened parts with different plastic layers; the plastic deformation characteristics of the plastic layer of the multiple strengthened parts correspond to the corresponding laser energy. Fretting fatigue tests were performed on the multiple reinforced components to obtain crack information of the multiple reinforced components; the crack information includes crack propagation characteristics; Based on multiple laser energies and crack information from multiple reinforced components, the primary influence relationship between laser energy and fretting fatigue life was determined. Based on the first influence relationship, the target laser energy is determined from the plurality of laser energies.

2. The method for optimizing fretting fatigue performance based on plastic layer regulation according to claim 1, characterized in that, Fretting fatigue tests were performed on the multiple reinforced components to obtain crack information of the multiple reinforced components, including: Fretting fatigue test is performed on each of the reinforced components to obtain image data of the fretting contact area. The image data is used to indicate multiple images of the fretting contact area from crack initiation to crack propagation. Based on the image data, the crack propagation characteristics of the corresponding reinforced component are determined; wherein, the crack propagation characteristics include the initial crack growth angle, the crack growth angle after deflection, and the crack length under polarization.

3. The method for optimizing fretting fatigue performance based on plastic layer regulation according to claim 2, characterized in that, The determination of the first influence relationship between laser energy and fretting fatigue life based on multiple laser energies and crack information of multiple strengthening components includes: A second influence relationship between laser energy and the plastic deformation characteristics of the plastic layer is obtained; wherein, the plastic deformation characteristics include grain size; Based on the initial crack growth angle, the crack growth angle after deflection, and the crack length during polarization, the crack growth rate of multiple strengthening components is determined. Based on the crack growth rate of the multiple reinforcing members and the plastic deformation characteristics of the plastic layer, a third influence relationship between the plastic deformation characteristics of the plastic layer and the crack growth rate is determined. Based on the second and third influence relationships, a first influence relationship between the laser energy and the fretting fatigue life is determined.

4. The method for optimizing fretting fatigue performance based on plastic layer regulation according to claim 3, characterized in that, The determination of the first influence relationship between the laser energy and the fretting fatigue life based on the second influence relationship and the third influence relationship includes: The second influence relationship was determined to be negative. The third influencing relationship was determined to be negative. Based on the second and third influence relationships, the first influence relationship between the laser energy and the fretting fatigue life is determined to be negative.

5. The method for optimizing fretting fatigue performance based on plastic layer regulation according to claim 3, characterized in that, Determining the target laser energy from the plurality of laser energies includes: The smallest of the plurality of laser energies is determined as the target laser energy.

6. The method for optimizing fretting fatigue performance based on plastic layer regulation according to any one of claims 1 to 5, characterized in that, Before performing surface strengthening of the micro-motion contact area of ​​the test piece based on multiple laser energies, the method includes: Determine the preset laser energy range; Multiple laser energies are determined from the preset laser energy range.

7. The method for optimizing fretting fatigue performance based on plastic layer regulation according to any one of claims 1 to 5, characterized in that, The method further includes: Obtain microstructure information of the plastic layer of multiple reinforced components; The microstructure information of multiple reinforcing components is simulated and reconstructed to obtain multiple polycrystalline structure models with grain structures on the surface. Based on the equivalent plastic strain value and / or dislocation density of the polycrystalline structure model, the fretting fatigue crack behavior of the polycrystalline structure model is determined. The fretting fatigue crack behavior based on multiple polycrystalline structure models was used to simulate and verify the target laser energy.

8. The method for optimizing fretting fatigue performance based on plastic layer regulation according to any one of claims 1 to 5, characterized in that, The method further includes: Based on the crack information of multiple strengthening components, the strain distribution of different plastic layers was obtained; Based on the strain distribution of different plastic layers, a predictive model for the fretting fatigue performance of plastic layers is constructed.

9. A parameter determination device based on the regulation of fretting fatigue properties using a plastic layer, characterized in that, include: The module is used to perform surface strengthening on the micro-motion contact area of ​​the test piece based on multiple laser energies, resulting in multiple strengthened parts with different plastic layers; wherein, the plastic deformation characteristics of the plastic layers of the multiple strengthened parts correspond to the corresponding laser energies; The module is used to perform fretting fatigue tests on the multiple reinforced components to obtain crack information of the multiple reinforced components; the crack information includes crack propagation characteristics; The first determining module is used to determine the first influence relationship between laser energy and fretting fatigue life based on multiple laser energies and crack information of multiple strengthening components. The second determining module is used to determine the target laser energy from the plurality of laser energies based on the first influence relationship.

10. An electronic device comprising a memory, a processor, and a computer program stored in the memory and executable on the processor, characterized in that, When the processor executes the computer program, it implements the micro-motion fatigue performance optimization method based on plastic layer regulation as described in any one of claims 1 to 8.